Implementasi PMA Nomor 20 Tahun 2019 tentang Pencatatan Nikah mengenai Pemeriksaan Dokumen di KUA Kecamatan Garut Kota - Seilla Nur Amalia Firdaus; Titin Suprihatin Suprihatin; Encep Abdul Rojak Rojak (UNISBA Press, 2022)
Abstract. Examination of marriage documents is carried out with the aim that in the process of registering a marriage there are no violations. As examples, having more than one wife without the court's permission, falsified marriage age limits, forced marriages and so on. When violations occur, it is worth asking whether the marriage document has been properly examined by the employee concerned or not. As happened in the District Kua Garut City, examination of documents does not present a prospective husband/wife and Guardian. This study aims to determine the implementation of PMA No. 20 Tahun 2019, which is concerning Marriage Registration regarding the practice of examining documents. This research uses case study and juridical-normative approaches. Primary data sources are obtained from legislation and interviews. Secondary data sources are obtained from books, journals and other scientific works. As for data analysis is using flow chart analysis method. As for data analysis is using flow chart analysis method. The results of the study concluded that the practice of examining documents at the KUA of Garut Kota Subdistrict, in general, was in accordance with PMA No. 20 of 2019 except for inspections by presenting prospective husbands/wives and guardians to ensure that there were no obstacles to marriage. This is not in accordance with the rules because the examination is carried out during the registration of the marriage will. Which is not every registration of marriage will be attended by prospective husband/wife and guardians. Abstrak. Pemeriksaan dokumen nikah dilakukan dengan tujuan agar dalam proses pencatatan perkawinan tidak terjadi pelanggaran, misalnya beristeri lebih dari satu orang tanpa izin pengadilan, batas usia menikah yang dipalsukan, menikah dengan paksaan dan lain-lain. Ketika pelanggaran terjadi, patut dipertanyakan apakah pemeriksaan dokumen perkawinan sudah dilakukan dengan baik oleh pegawai yang bersangkutan. Seperti yang terjadi di KUA Kecamatan Garut Kota, pemeriksaan dokumen tidak menghadirkan calon suami/istri serta wali. Penelitian ini bertujuan untuk mengetahui implementasi PMA No. 20 Tahun 2019 Tentang Pencatatan Nikah mengenai praktik pemeriksaan dokumen. Penelitian ini menggunakan pendekatan case study dan yuridis-normatif. Sumber data primer diperoleh dari perundang-undangan dan hasil wawancara. Sumber data sekunder diperoleh dari buku, jurnal dan karya ilmiah lainnya. Analisis data menggunakan metode flow chart analysis. Hasil penelitian menyimpulkan bahwa praktik pemeriksaan dokumen di KUA Kecamatan Garut Kota pada umumnya sudah sesuai dengan PMA No. 20 Tahun 2019 kecuali pemeriksaan dengan menghadirkan calon suami/istri serta wali untuk memastikan tidak ada halangan menikah, hal tersebut tidak sesuai dengan aturan karena pemeriksaan dilakukan ketika pendaftaran kehendak nikah. Yang mana tidak setiap pendaftaran kehendak nikah dihadiri oleh calon suami/istri serta wali.